III.–The Elasticity of Substitution and the Incidence of an Imperial Inhabited House Duty - Meade, J. E. (Review of Economic Studies, 1934)
Notes on the Elasticity of Substitution: III.—The Elasticity of Substitution and the Incidence of an Imperial Inhabited House Duty Get access J. E. Meade J. E. Meade Hertford College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 149–152, https://doi.org/10.2307/2967623 Published: 01 February 1934